Controllable self-assemblies of sodium benzoate in different solvent environments1. Issue 86 (18th September 2015) - Ma, Mingfang; Gu, Jinge; Yang, Minmin; Li, Zhaolou; Lu, Zhuoqun; Zhang, Yimeng; Xing, Pengyao; Li, Shangyang; Chu, Xiaoxiao; Wang, Yajie; Li, Qi; Lin, Minyan; et al.
<x xml:space="preserve">Abstract</x> Sodium benzoate is an important and widely used food additive, however, it's self-assembly properties in diverse solvents have been rarely studied. Here, we systematically report its various self-assemblies in different solvents environments.